Novel Agents in the Management of Pancreatic Adenocarcinoma: Phase I Studies - Dimou, Anastasios T; Syrigos, Konstantinos N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
Pancreatic adenocarcinoma has repetitively proved refractory to chemotherapy and biologic compounds with only a few drugs offering limited benefit. A number of novel regimens has been tested in phase I trials and reported recently in the 2011 American Society of Clinical Oncology (ASCO) Gastrointestinal Cancers Symposium. Specifically, a novel mitogen-activated protein kinase kinase (MEK) inhibitor, a connective tissue growth factor inhibitor, a coagulase factor VIIa inhibitor, as well as adenovirus delivery of herpes simplex virus thymidine synthase gene followed by anti-herpetic treatment have all proven to be safe in pancreatic cancer patients. Phase II trials will provide further evidence whether they can become clinically relevant in the future. Image: Yale University School of Medicine. New Haven, CT, USA (logo).